PENGARUH METODE DEMONSTRASI TERHADAP KEMAMPUAN IBU MELAKUKAN TEPID SPONGE PADA ANAK DENGAN DEMAM DI RSUD CIBABAT CIMAHI - Rini Mulyati; Nyai Junengsih; Argi Virgona (NHM PRESS, 2022)
The purpose of this research is to know the effect of demonstration method on mother’s ability to do tepid sponge in children with fever. This research employed Pre–experiment research method with one group pre-test post-test design. Instrumen in this research using standard observation sheets with a score range 25-100. This research uses purposive sampling with 14 respondent who have a child with fever. The data were collected for 5 days by measuring the level of the mother’s ability to do tepid sponge before and after the demonstration. Respondents were given 3 times each 30 minutes demonstration in 1 meeting. Data analysis is presented in the form of univariate analysis to know the avarege and bivariate to know the influence by using t dependen test The research showed that the average score of respondent ability to do tepid sponge before the demonstration was 54,679 while after the demonstration was 79,643. Statistical results with t dependen test obtained p value 0,001 = α ≤ 0,05. This results showed there is effect of demonstration method on mother’s ability to do tepid sponge. Based on the description is suggested to the mother to be able to konw, understand, and implement tepid sponge as one effort to decrease fever in child besides giving antipyretic.